The Influence of Education and Training and Compensation on Teacher Performance Mediated by Loyalty - Gantang Suwarga; Taufiq Rahman; Surya Bintarti (Postgraduate, University of Mataram, 2024)
Education is carried out with the aim that the potential of students can develop, students become people who believe and are devoted to God Almighty, have noble morals, are in good health, have knowledge, are capable, have creativity, can be independent, and can become good citizens, responsible and democratic. Teachers who are passionate about teaching can easily improve their performance at work, providing compensation to teachers can also improve teacher welfare and have an impact on teacher performance. This research aims to determine the influence of education training and compensation on teacher performance mediated by loyalty. This research used a quantitative method with a population and sample of 170 teachers in the MTS Tambun Selatan sub-district. The research results show that education and training do not significantly affect teacher loyalty in MTS in Tambun Selatan District. Then compensation has a positive and significant effect on teacher loyalty in MTS throughout Tambun Selatan District. Education and training positively and significantly affect teacher performance in MTS throughout Tambun Selatan District. Compensation has a positive and significant effect on teacher performance in MTS throughout Tambun Selatan District. Teacher performance has a positive and significant effect on teacher loyalty in MTS throughout Tambun Selatan District.